"Different than an infantry unit down in Georgia": Narratives of queer liberation in the post-DADT military. (September 2018) - Connell, Catherine
More than five years out from its implementation, we still know relatively little about how members of the US military and its ancillary institutions are responding to the repeal of Don't Ask, Don't Tell. Contrary to what one might expect given the long history of LGBTQ antipathy in the military, I found in interviews with Boston area Reserve Officer Training Core (ROTC) cadets unanimous approval for the repeal of DADT. When pressed to explain why there was so much homogeneity of favorable opinion regarding the repeal, interviewees repeatedly offered the same explanation: that Boston, in particular, is such a progressive place that even more conservative institutions like the ROTC are spared anti-gay sentiment. They imagined the Southern and/or rural soldier they will soon encounter when they enter the US military, one who represents the traditionally homophobic attitudes of the old military in contrast to their more enlightened selves. This "metronormative" narrative has been critiqued elsewhere as inadequate for understanding the relationship between sexuality and place; this article contributes to that critique by taking a new approach. Rather than deconstruct narratives of queer rurality, as the majority of metronormativity scholarship has done, I deconstruct these narratives of urban queer liberation. I find that such narratives mask the murkier realities of LGBTQ attitudes in urban contexts and allow residents like the ROTC cadets in this study to displace blame about anti-gay prejudice to a distant Other, outside of their own ranks.